PEMIKIRAN EKONOMI ISLAM IBNU KHALDUN DAN RELEVANSI KONSEP AL-MUQADDIMAH BAGI ANALISIS KONTEMPORER - Khaulah Azizah; Lina Marlina Susana (Al-Iqtisodiyah : Jurnal Ilmu Ekonomi dan Ekonomi Islam, 2026)
This journal aims to explore in detail the contributions of Ibn Khaldun, a 14th-century Islamic scholar and polymath, to economics, particularly Islamic economics. Through his renowned work, the Muqaddimah, Ibn Khaldun established a foundation for economic theory far ahead of its time, including ideas on the value of labor, the functioning of markets, cultural cycles related to the economy, taxes, and the function of government. The findings of this study demonstrate that Ibn Khaldun’s thought not only has a historical-normative dimension but is also highly relevant to addressing current economic issues such as social injustice, budgetary policy, and sustainable economic growth.